NUMERICAL MODELING OF WAVE-ICE INTERACTION WITH A SINGLE SUPPORT - Izmail Kantarzhi; Maksim Afonyushkin (International Journal for Computational Civil and Structural Engineering)
The change in the joint wave-ice load acting on a freestanding hydraulic structure under conditions of ice freezing to the support is considered. The existing scientific works on this problem were analyzed and the appropriate research method was chosen. The topic of the article is relevant in the light of active development of the Arctic part of Russia and construction of new hydraulic structures, which require more accurate methods of determining ice and wave loads. The novelty of the work lies in the analysis of the joint impact of the wave and ice floe on the structure. Numerical modeling in LS-DYNA program and analytical methods presented in normative documents were used for the study. Verification of the model by loads was performed by comparing numerical data with the results of analytical calculation. Changes in the horizontal forces of wave and ice floe pressure on the structure, as well as the wave impact on the ice floe were obtained. Dependences of changes in these forces and their ratios on the ice floe length were plotted. In the course of analyzing the results it was determined that the ice floe pressure force on the structure changes most significantly. The cyclic character of changes in the wave and ice forces was also revealed. Presumably, this is due to the dynamic nature of ice breakup and the effect of "ice floe surfacing-submergence". In further research, it is recommended to apply the developed model for different scenarios involving other types of ice and types of structures. The results of the paper can be used to develop more accurate methods for analytical calculation of the impact of waves and ice on structures.